Reliability and performance analysis of a high step-up DC–DC converter with a coupled inductor for standalone PV application. Issue 12 (14th October 2020) - Divya Navamani, J.; Vijayakumar, K.; Jegatheesan, R.
ABSTRACT: In view of the major power crisis in fast developing countries, we introduce a quadratic boost converter with coupled inductor for standalone photovoltaic (PV) application, and their respective voltage gain is derived. The features of this proposed topology are studied with the help of steady state analysis and its superiority is proved by comparing it with the existing coupled inductor based topologies. The reliability study is carried out for the proposed topology with its working condition. Also, simulation is performed in the NL5 simulator, and the results are presented. A 40 W prototype of the same is built to showcase the desired output of the proposed converter.